Direito penal e constituição: uma leitura do direito penal no estado democrático de direito - Abraão, Eduardo Pião Ortiz (2010)
This essay has as its purpose to promote an analysis of the Criminal Law facing the Democratic Law State, established by the 1988 Constitution edition. Starting from a historical foreshortening concerning the State´s structure and evolution, from a brief run-down on the founded structures during the ancient and medieval times, it brings to the consecration of the State of Rights and, consequently, later on the transcending of liberal and social prototypes, to the Democratic Law State. In its democratic State form, it is essential and indispensable to verify which juridical interests and assets that must be tutored by the Criminal Law within this state archetype. The search for delimitation of the penal assets, therefore, must be a constant concern while analyzing Criminal Law under the Federal Constitution. The crimination commandments enclosed in the Constitution play important role in the penal assets definition context, once their aim is to point specific subjects that must be fulfilled in the Criminal field. Therefore, once criminal commandments are known, the task in order to discipline, in the Criminal range, the matters under constitutional crimination, is compulsory, as there´s no other option left to the ordinary legislator. It´s also relevant to point that nowadays Criminal Law has to present itself under two different aspects, inasmuch as criminality in the present reaches not only traditional, individual juridical rights and assets but also diffuse and group ones, showing a new feature that demands concept and dogma renewal in Criminal Law. It´s necessary to provide the State with instruments capable of effectively fight crimes that hit transindividual rights as well as related conducts like organized crime, terrorism, pedophilia, money laundering activities etc. - that appear as worthy of a distinguished handling by the penal legislation. To such an extent, traditional Criminal Law should stay circumscribed to facing offenses that compound the so-called mass criminality, as for example, homicide, injury, theft, robbery, fraud etc., because in a way it can be seen as an effective solution to those misdemeanors. However, considering delicts against diffuse and group rights, money laundering, pedophilia, terrorism, organized crime, it´s necessary for the Criminal Law to submit itself through reorganization, which would legally provide the suitable competent instruments and implements to fight this kind of criminality. This essay will focus, mainly within this ambivalent conception of the Criminal Law, the search of an appropriate scrutiny on the Criminal Law inserted in the Democratic Law State